2008
DOI: 10.1113/expphysiol.2008.043216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac hypertrophy on arterial and cardiopulmonary baroreflex control of renal sympathetic nerve activity in anaesthetized rats

Abstract: This study aimed to quantify the effect of cardiac hypertrophy induced with isoprenaline and caffeine on reflex regulation of renal sympathetic nerve activity by the arterial and cardiopulmonary baroreceptors. Male Wistar rats, untreated or given water containing caffeine and subcutaneous (s.c.) isoprenaline every 72 h for 2 weeks or thyroxine s.c. for 7 days, were anaesthetized and prepared for measurement of renal sympathetic nerve activity or cardiac indices. Both isoprenaline-caffeine and thyroxine treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(51 reference statements)
2
15
2
2
Order By: Relevance
“…LVH was induced with subcutaneous injections of isoprenaline (5.0 mg·(kg body mass) -1 ) on days 1, 4, 7, 10, and 13 of the study, and caffeine was administered orally (62 mg·L -1 in the drinking water, daily for 14 days). This approach is a modification of a previously reported model whereby similar doses of isoprenaline were utilised but only 4 injections were administered (Flanagan et al 2008). The modification in the dosage regimen is based on our preliminary pilot studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LVH was induced with subcutaneous injections of isoprenaline (5.0 mg·(kg body mass) -1 ) on days 1, 4, 7, 10, and 13 of the study, and caffeine was administered orally (62 mg·L -1 in the drinking water, daily for 14 days). This approach is a modification of a previously reported model whereby similar doses of isoprenaline were utilised but only 4 injections were administered (Flanagan et al 2008). The modification in the dosage regimen is based on our preliminary pilot studies.…”
Section: Methodsmentioning
confidence: 99%
“…This model can be induced experimentally by chronic administration of a combination of isoprenaline and caffeine (Flanagan et al 2008;Buckley and Johns 2011). Caffeine is reported to increase plasma levels of noradrenaline, whereas isoprenaline increases heart rate and work load by stimulating cardiac ␤-adrenoceptors (Graham and Spriet 1995;Kovanecz et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that increasing circulatory volume leads to a fall in renal sympathetic nerve activity (RSNA), and vice versa, and has been termed the cardiopulmonary reflex. Interestingly, in two models of cardiac hypertrophy induced by isoprenaline/ caffeine or thyroxine exposure, it was found that the reflex renal sympathoinhibition in response to an acute saline volume load did not occur (4). This implied a deficit in the reflex residing either in the heart or within central pathways.…”
mentioning
confidence: 99%
“…*P Ͻ 0.01, compared with innervated kidney. involving 1-wk administration of thyroxine, which has been previously shown to cause a cardiac hypertrophy associated with a blunted renal sympathoinhibitory response to a saline load (4). Importantly, the cardiac hypertrophy enhanced function as cardiac contractility was increased in the isoprenaline/ caffeine model (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation